2012
DOI: 10.1504/ijiq.2012.050036
|View full text |Cite
|
Sign up to set email alerts
|

A total data quality management for credit risk: new insights and challenges

Abstract: Recent studies indicated that companies are increasingly experiencing data quality (DQ) related problems resulting from their increased data collection efforts. Addressing these concerns requires a clear definition of DQ but typically, DQ is only broadly defined as 'fitness for use'. While capturing its essence, a more precise interpretation of DQ is required during measurement. While there is a growing consensus on the multi-dimensional nature of DQ, no exact DQ definition has been put forward due to its cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…Another operational advantage of this type of data concerns data quality (Moges et al 2012): typically this is a major challenge when working with structured data. With payment data, however, no such issues arose: a simple "dump" from the transaction log is all that is needed for the BeSim method to be applied.…”
Section: Expert Feedbackmentioning
confidence: 99%
“…Another operational advantage of this type of data concerns data quality (Moges et al 2012): typically this is a major challenge when working with structured data. With payment data, however, no such issues arose: a simple "dump" from the transaction log is all that is needed for the BeSim method to be applied.…”
Section: Expert Feedbackmentioning
confidence: 99%
“…In this article, we validate our work analyzing a large case study from a financial institution, focusing on evaluating the probability of default, which is one of the main components of risk analysis. In the literature, the challenges of data quality in credit risk evaluation processes have been discussed in Moges et al (2012). In particular, the paper illustrates the main quality dimensions considered relevant by stakeholders and identifies accuracy as the main issue in this context.…”
Section: Related Workmentioning
confidence: 99%
“…We define it as a process that, on the basis of given inputs, provides as output an assessment (denoted as Process Outcome, y) that is a ranking or a rating for an object under investigation on a given scale of values. As discussed in the related work, this type of assessment is typical of decision-making processes, such as in financial institutions (Moges et al 2012). For instance, objects of investigation in a financial institution are the customers asking for credit to whom a rating is associated, which is used as a basis for decision making.…”
Section: Scenario: Scoring Processesmentioning
confidence: 99%
“…Shankaranarayanan et al [38] used a percentage DQM representation where the quality level of the data represented with an 80% accuracy or completeness level is better than the quality of data represented by a 70% level. Moges et al [24] conducted a pilot study to evaluate DQM representations by using two different types of DQM formats. These are DQM with lower and upper value limits (range representation) and probability representation.…”
Section: Graphicalmentioning
confidence: 99%
“…Moreover, the impact of DQM on decision outcomes can be negative. In response, prior DQM research investigated the use of DQM for decision making processes, although there is no full consensus on the results [4,9,23]. Some researchers have found that DQM is used in certain situations [9], and others didn't find any statistical evidence that DQM is actually used, even when it is available [34].…”
Section: Introductionmentioning
confidence: 99%